Managing successful universities - Shattock, Michael; Society for Research into Higher Education (Maidenhead : Open University Press, 2010)
This book describes the principles involved in managing universities so that they are successful in the modern era.
Previous ed.: 2003.
Published in association with the Society for Research into Higher Education.
Includes bibliographical references (p. [204]-212) and index.
Keywords: Universities and colleges -- Great Britain -- Administration